Status report on the teaching of non-linguistic subjects in French at fundamental school in Burundi - Sinabajije, Wenceslas; Bento, Margaret (Applied mathematical sciences, 2022)
Research on the transfer of knowledge in sessions of Civic and Human Formation lessons in the 5th fundamental year in Burundi was carried out to understand the modalities of managing the linguistic transition from Kirundi to French. The transfer of knowledge should be exclusively in French and no longer in the mother tongue as in the 1st to 4th-year classes. To achieve the desired results, we attended the lesson sessions until the data were saturated. After analyzing the data and interpreting the results, we noted that the majority of teachers taught lessons in French and Kirundi equally or only in their mother tongue. Some were coining words in Kirundi due to a lack of existing scientific terms. There was therefore a misuse of language in both French and Kirundi. The transfer problems identified included lack of motivation, lack of initiative for the use of French, failure to apply the recommended approach, failure to respect time limits, and lack of practical exercises to check if objectives had been achieved.